Orbital Infarction due to Sickle Cell Disease without Orbital Pain - Cameron L. McBride; Kim-Binh T. Mai; Kartik S. Kumar (Case Reports in Ophthalmological Medicine)
Sickle cell disease is a hemoglobinopathy that results in paroxysmal arteriolar occlusion and tissue infarction that can manifest in a plurality of tissues. Rarely, these infarcted crises manifest in the bony orbit. Orbital infarction usually presents with acute onset of periorbital tenderness, swelling, erythema, and pain. Soft tissue swelling can result in proptosis and attenuation of extraocular movements. Expedient diagnosis of sickle cell orbital infarction is crucial because this is a potentially sight-threatening entity. Diagnosis can be delayed since the presentation has physical and radiographic findings mimicking various infectious and traumatic processes. We describe a patient who presented with sickle cell orbital crisis without pain. This case highlights the importance of maintaining a high index of suspicion in patients with known sickle cell disease or of African descent born outside the United States in a region where screening for hemoglobinopathy is not routine, even when the presentation is not classic.